Effect of procrastination and online homework distractors on research motivation and scientific output in Peruvian university students - Mamani-Benito, Oscar (2025)
Purpose: This study seeks to examine the relationship between online task distractions, academic procrastination, and students’ motivation toward research engagement and scientific output at the university level. Materials and methods: An explanatory study was carried out with a sample of 489 university students from two higher education institutions in Lambayeque, Peru. The data were gathered through the administration of three instruments: the Research Motivation Scale (MoINV-U), the Online Homework Distraction Scale (OHDS), and the Academic Procrastination Scale (EPA). Results: The findings indicate that online task distractions have a positive effect on the postponement of academic activities (H1) and on students’ academic self-regulation (H3). Similarly, the analysis revealed that academic self-regulation exerts a positive effect on motivation toward research and scientific production (H4), while the postponement of activities showed no significant effects (H2). Conclusion: Structural equation modeling (SEM) confirmed the validity of the proposed relationships, revealing significant effects among the variables, except for the relationship between task postponement and motivation for research and scientific production.